Analisis Rendahnya Minat Baca Mahasiswa - Zai, Mardin Syah Putra; Zai, Trisna Wati (CV. SINAR HOWUHOWU, 2025)
This research aims to examine the low interest in reading among Nias University students. Several factors that influence the low interest in reading are the development of digital technology, dependence on instant information via the internet, and the perception that reading is boring and takes up a lot of time. The research results show that students read entertainment content such as novels and comics more often than textbooks. Efforts to increase interest in reading must include promoting a reading culture, providing access to interesting reading materials, as well as support from the campus environment. It is hoped that this research can provide a solution in increasing students' reading interest.